The baby dances - Henderson, Kathy; Kerins, Tony (Cambridge, MA Candlewick Press, 1999)
Recounts the development of a baby, from birth to rolling over, crawling, standing, and finally walking
02/2006, unk
Keywords: Babies -- Fiction; Growth -- Fiction